Floristic and edaphic inventory of Atlantic riparian forests: references for restoration projects - Wénita de S. Justino; Daniel Negreiros; Letícia Ramos; João C. G. Figueiredo; Dario C. Paiva; Yumi Oki; Rubens M. dos Santos; Lorena Ashworth; Yule R. F. Nunes; G. Wilson Fernandes (Nature Conservation Research: Заповедная наука)
The use of reference ecosystem inventories to guide ecological restoration is essential for monitoring the success of environmental recovery. The aim of this study was to carry out a floristic and edaphic inventory in old growth riparian forest remnants from the upper River Doce watershed, to provide subsidies for restoration programmes. The study was carried out in the municipalities of Rio Casca, Sem-Peixe, and Santa Cruz do Escalvado. The most representative families in species richness were Fabaceae, Meliaceae, Sapindaceae, Bignoniaceae, and Salicaceae. Based on the chemical properties of the soils, there was considerable heterogeneity among plots, with soils ranging from acidic to neutral (pH 3.8–6.3), with variable contents of phosphorus (0.0–7.6 mg × dm-3), and aluminum saturation (0.0–66.5%), among other factors. The co-inertia analysis showed a highly significant connection of 51.5% (p < 0.001) between floristic and edaphic matrices in tree stratum, and 46.5% (p < 0.001) between floristic and edaphic matrices in the sapling stratum. The reference ecosystems presented here suggest that action plans aimed at recovering the riparian forest should consider the edaphic conditions and its relationship with the plant community on a regional scale, avoiding the extrapolation of observed pattern of taxon-environment relationships to other regions.